2014
DOI: 10.1007/s12274-014-0616-7
|View full text |Cite
|
Sign up to set email alerts
|

Nanophase separation and structural evolution of block copolymer films: A “green” and “clean” supercritical fluid approach

Abstract: Type of publicationArticle (peer-reviewed)Link to publisher's version http://dx.doi.org/10.1007/s12274-014-0616-7Access to the full text of the published version may require a subscription. Rights © Tsinghua University Press and Springer-Verlag Berlin Heidelberg2014. This is a pre-print of an article published in Nano Research. hexagonally ordered films were demonstrated using a supercritical fluid process at low temperatures and pressures. Predominant swelling of PEO domain in scCO2 induces nanophase separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The increased disparity between the CO 2 –PS and CO 2 –PEO solubility and interfacial energies at high temperatures creates larger effective interaction parameter ( χ eff ) irrespective of the film thickness, eases the process of phase separation. Previous reports suggests that the temperatures below 50 °C are more suitable to achieve phase separation under constant CO 2 pressure conditions, consistent with our finding [ 27 , 32 ]. At a temperature of 60 °C, which is just above the melting temperature of the PEO block (55 °C) for the S3 molecular weight system, PEO is in a semi-molten state which facilitates the reorientation of the PEO cylinders and the morphological change [ 35 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The increased disparity between the CO 2 –PS and CO 2 –PEO solubility and interfacial energies at high temperatures creates larger effective interaction parameter ( χ eff ) irrespective of the film thickness, eases the process of phase separation. Previous reports suggests that the temperatures below 50 °C are more suitable to achieve phase separation under constant CO 2 pressure conditions, consistent with our finding [ 27 , 32 ]. At a temperature of 60 °C, which is just above the melting temperature of the PEO block (55 °C) for the S3 molecular weight system, PEO is in a semi-molten state which facilitates the reorientation of the PEO cylinders and the morphological change [ 35 ].…”
Section: Resultssupporting
confidence: 93%
“…Vertical orientation represents least entropically hindered route for microphase separation, since the PEO cylinder length is limited to the thickness of the films. Previous studies have shown that the swelling of PEO in scCO 2 is between 20–25 wt%, larger than that of PS (5–6 wt%) at similar pressure of 1400 psi [ 27 , 31 , 32 , 33 ]. Thus, the swelling of the entire film is dominated by the swelling of the PEO microdomains compared to the PS block.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of techniques, including as chemo- and grapho-epitaxy, shear flow, and electric and geometric fields have been employed to produce patterns with well-defined orientational and positional order in block copolymer thin films with different architectures. ,− Due to its simplicity and low cost, solvent annealing techniques are one of the most promising approaches to control long-range order and symmetry of block copolymer patterns. In particular, previously, we found that annealing under supercritical carbon dioxide (scCO 2 ) speeds up the mechanisms of coarsening and stabilizes hexagonal patterns with a degree of order, which is unreachable with conventional thermal annealing techniques. , Considering its low cost, wide availability, moderate critical conditions (critical temperature T C = 31 °C, critical pressure P C = 73.8 bar, and critical density ρ C = 0.468 g/cm 3 ), gas-like diffusivity, and low interfacial tension with the polymers, supercritical carbon dioxide, scCO 2 , is increasingly being used as a green solvent in different fields, including biomedical applications, polymer processing, and polymer synthesis. …”
Section: Introductionmentioning
confidence: 99%
“…In general, solvent annealing techniques employ organic or halogenated solvents, even though they are usually toxic and have a negative environmental impact . As an alternative, supercritical carbon dioxide (scCO 2 ) is increasingly being used as a green solvent in different fields, including biomedical applications, polymer processing, and polymer synthesis. In addition to its low cost, wide availability, and to the moderate critical conditions (critical temperature T C = 31 °C, critical pressure P C = 73.8 bar and critical density ρ C = 0.468 g/cm 3 ) CO 2 also offers a number of further advantages: (i) it is a poor solvent for most polymers and although its equilibrium sorption is modest, it can be controlled by pressure; (ii) it has a gas-like diffusivity, therefore the diluent rapidly reaches an equilibrium state in thin polymer films; and (iii) it has low interfacial tension with the polymers, and the gas can be eliminated completely after the termination of the process. …”
Section: Introductionmentioning
confidence: 99%